2010
DOI: 10.18632/oncotarget.188
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt/mTOR Pathway - Beyond Rapalogs

Abstract: AbstrAct:It is well established that the PI3K pathway plays a central role in various cellular processes that can contribute to the malignant phenotype. Accordingly, pharmacological inhibition of key nodes in this signaling cascade has been a focus in developmental therapeutics. To date, agents targeting upstream receptor tyrosine kinases are best studied and have achieved greatest clinical success. Further downstream, despite efficacy in certain tumor types, the rapalogs have been somewhat disappointing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(143 citation statements)
references
References 82 publications
2
136
0
5
Order By: Relevance
“…A positive feedback loop on the Akt pathway by rapalogs has been previously described in other cell types [21]. Based on this, we studied the impact of everolimus on Akt and ERK activation on three randomly selected tumors.…”
Section: Everolimus Decreased Meningioma Cell Viability But Activatementioning
confidence: 82%
See 1 more Smart Citation
“…A positive feedback loop on the Akt pathway by rapalogs has been previously described in other cell types [21]. Based on this, we studied the impact of everolimus on Akt and ERK activation on three randomly selected tumors.…”
Section: Everolimus Decreased Meningioma Cell Viability But Activatementioning
confidence: 82%
“…On merlin-deficient schwannomas, everolimus was ineffective for the treatment of progressive tumors from 10 patients [29]. Consequently, for blocking this positive feedback, a concomitant inhibition of both Pi3K and mTOR or Pi3K alone has been attempted [21].…”
Section: Mtor Inhibitors Effect On Meningiomasmentioning
confidence: 99%
“…PIK3CA mutations have been detected in various frequencies (4-25 %) of GC [21,22], but a recent biomarker analysis in a prospective clinical trial showed low rate of the mutation [23]. & Constitutive activation of PI3K caused by activating PIK3CA mutations, reduced PTEN expression, or deregulated signaling can induce resistance to HER2 inhibition [24,25]. Collectively, PI3K inhibition warrants evaluation in EBV-positive GC.…”
Section: Ebv-infected Tumorsmentioning
confidence: 99%
“…Inhibitors of mTORC1 (rapamycin and its analogs, or "rapalogues") have shown activities in RCC patients. Two of such agents, temsirolimus (CCI-779) and everolimus (RAD001), were approved by USA FDA for treatment of advanced or recurrent RCC; however, their efficacy is thought to be limited by feedback loops and cross talk with other pathways, leading to the development of drug resistance [7].…”
mentioning
confidence: 99%